Legal Aspects of Patenting and Information Support - Kuruvilla, P. K. (Journal of Information and Knowledge, 1981)
Discusses the nature of patents and the patent acts prevalent in India. Patent office’s organisation kinds of patents, kinds of inventions amenable for patent deed, are discussed. Details of patent claiming procedures such as patent filing specifications, patent examination, patent grant rejection, legal aspects of patenting, ascertaining "novelty" of invention, are presented. After pointing out the need for scientific and technical information, discusses briefly the organisational structure for an information centre of a patent office. Also high-lights some problems in the Indian Patent Act.